HUBUNGAN PENGETAHUAN DENGAN ANEMIA IBU HAMIL DI PUSKESMAS SELATBARU KECAMATAN BANTAN KABUPATEN BENGKALIS TAHUN 2024 - Putri Susanti, Woro; Tanberika, Fajar Sari; Yanti, Rifa; Ekdani Aifa, Wira (Ensiklopedia of Journal, 2025)
Anemia in pregnant women is the biggest and most difficult micronutrient problem to overcome throughout the world. Anemia not only affects mothers, babies born to mothers who suffer from iron deficiency or anemia are likely to have little or no iron reserves at all. in the body even though they do not suffer from anemia. The aim of this research is to determine the relationship between knowledge and anemia in pregnant women at the Selatbaru Community Health Center, Bantan District, Bengkalis Regency. The research method is descriptive correlational with a cross sectional approach. The population in this study was 129 pregnant women who visited from January to August 2024 at the Selatbaru Community Health Center and the sample used an accidental sampling technique of 35 respondents. This research instrument uses a questionnaire, data analysis techniques use the Chi Square test. The research results showed that the majority of respondents experienced anemia, 27 people (77.1%), the majority of respondents had insufficient knowledge about anemia during pregnancy, 21 people (60.0%). The results of the Chi Square test showed that there was knowledge (p-value=0.037) of the incidence of anemia at the Selatbaru Community Health Center, Bantan District, Bengkalis Regency. Suggestions for health workers to be more active in providing health education to the public regarding maternal health, especially regarding anemia in pregnancy.Keywords  : Knowledge, pregnant women, anemia in pregnancy.